The Influence of Knowledge, Religiosity, Company Image, and Trust on Customer Interest in Saving at KSPPS BMT Tazakka Bojong - Awalia, Wina; Shultoni, Muhammad; Adinugraha, Hendri Hermawan (ZISWAF ASFA, 2023)
This research was motivated by the knowledge of BMT Tazakka Bojong KSSPPS customers who did not know much about Sharia financial institutions, even though there are many services at BMT Tazakka KSPPS that customers can use, one of which is a high-cost and popular savings product. A financial interest is a person's interest in a particular financial product.  Interest will arise from a visual or conceptual view of the product so that the group's plans can determine their investment decision. This study used statistical methods using SPSS software.  The population of this study was the management of KSPP BMT Tazakka Bojong, with a sample of 94 respondents.  The sampling method uses purposive sampling, and the data collection method uses questionnaires.  The results showed that diversity of knowledge, religion, and beliefs had a positive effect, while the company's image variable did not have a significant effect. The diversity of religious knowledge, company image, and beliefs positively and significantly influences interest.